Brief Comprehensive Quality of Life Assessment After Stroke: The Assessment of Quality of Life Instrument in the North East Melbourne Stroke Incidence Study (NEMESIS) - Sturm, Jonathan W.; Osborne, Richard H.; Dewey, Helen M.; Donnan, Geoffrey A.; Macdonell, Richard A.L.; Thrift, Amanda G. (Stroke (1970), 2002)
Background and Purpose— Generic utility health-related quality of life instruments are useful in assessing stroke outcome because they facilitate a broader description of the disease and outcomes, allow comparisons between diseases, and can be used in cost-benefit analysis. The aim of this study was to validate the Assessment of Quality of Life (AQoL) instrument in a stroke population. Methods— Ninety-three patients recruited from the community-based North East Melbourne Stroke Incidence Study between July 13, 1996, and April 30, 1997, were interviewed 3 months after stroke. Validity of the AQoL was assessed by examining associations between the AQoL and comparator instruments: the Medical Outcomes Short-Form Health Survey (SF-36); London Handicap Scale; Barthel Index; National Institutes of Health Stroke Scale; and Irritability, Depression, Anxiety scale. Sensitivity of the AQoL was assessed by comparing AQoL scores from groups of patients categorized by severity of impairment and disability and with total anterior circulation syndrome (TACS) versus non-TACS. Predictive validity was assessed by examining the association between 3-month AQoL scores and outcomes of death or institutionalization 12 months after stroke. Results— Overall AQoL utility scores and individual dimension scores were most highly correlated with relevant scales on the comparator instruments. AQoL scores clearly differentiated between patients in categories of severity of impairment and disability and between patients with TACS and non-TACS. AQoL scores at 3 months after stroke predicted death and institutionalization at 12 months. Conclusions— The AQoL demonstrated strong psychometric properties and appears to be a valid and sensitive measure of health-related QoL after stroke.